Designing Enterprise Architecture for Vessel Services: A Case Study of PT Pelindo Jasa Maritim - Ariatama, Triswiza; Purwandari , Betty; Satria , Riri (International Journal of Advances in Data and Information Systems, 2026)
PT Pelindo Jasa Maritim (SPJM), as one of the subholdings of PT Pelabuhan Indonesia (Pelindo) providing marine and port supporting services, requires information technology to support service integration in line with the company’s strategic directions. Using the TOGAF framework, this study identifies five main business service clusters: Marine Services (Pilotage and Towage), Crewing, Port & Equipment Services, Dredging & Shipyard, and Utilities. Each cluster is designed to be supported by a single standardized core application that reflects the strategic direction of “one main application per cluster.” The proposed architecture combines a hybrid cloud approach with Internet of Things (IoT) technologies to enable advanced analytics and data-driven decision making. Data were collected through document analysis, interviews with key stakeholders, and observation of core business processes. This study adopts a Design Science Research (DSR) approach and evaluates the EA blueprint through expert-based validation against alignment, completeness, and implementation feasibility criteria. The study results in an enterprise architecture blueprint that defines the role of core applications for each service cluster and specifies the supporting technology platforms required to realize strategic directions. The design can serve as a reference for companies in the maritime industry..